2016
DOI: 10.1002/cctc.201501225
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin‐Grafted Silica‐Supported Pd Nanoparticles: An Efficient and Versatile Catalyst for Ligand‐Free C−C Coupling and Hydrogenation

Abstract: Silica is an extremely versatile support, which is capable of hosting metal nanoparticles (NPs) and enhancing their stability and reactivity. In this study, a novel cyclodextrin/silica support for Pd NPs, which we have denoted Pd/Si‐CD, has been prepared. The highly efficient and homogeneous impregnation of small palladium nanoparticles on this support has been carried out under conventional conditions, and ultrasound irradiation has been shown to have a beneficial effect on catalyst preparation. The catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…On the basis of our experience with covalently-functionalized silica [54,55], the modification of silica surfaces via the grafting of organic compounds can lead to improve catalytic activity and may increase sorption capacity. With the aim of obtaining different silica-support-grafted β-CDs for Cu(II) species using a short and reliable synthetic protocol, two different routes were compared.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our experience with covalently-functionalized silica [54,55], the modification of silica surfaces via the grafting of organic compounds can lead to improve catalytic activity and may increase sorption capacity. With the aim of obtaining different silica-support-grafted β-CDs for Cu(II) species using a short and reliable synthetic protocol, two different routes were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Martina et al have reported [102] the synthesis of a novel cyclodextrin/silica support to host Pd nanoparticles with enhanced stability and reactivity, according to Scheme 47. The authors ascribed the formation of homogeneously dispersed Pd nanoparticles of small size to the presence of a coordinating group.…”
Section: Solid Supported Pd Catalyzed Mw Promoted Smcmentioning
confidence: 99%
“…Silica is a remarkably versatile support and one that is able to host metal nanoparticles (NPs) and improve their reactivity and stability. Martina et al [102], have recently prepared a novel cyclodextrin/silica support for Pd NPs (Pd/Si-CD) (Scheme 45). Cyclodextrin (CD) grafting into an inorganic silica framework provided a hybrid organic/inorganic material suitable for further metal impregnation.…”
Section: Ultrasound Assisted Heterogeneous Catalyst Preparation For Mmentioning
confidence: 99%
“…However, in the last few years, the importance of palladium‐based heterogeneous catalytic systems has received significant attention because of their facile recovery and reusability. Precedently, carbon, [ 7 ] magnetic materials, [ 8 ] silica, [ 9 ] hydroxyapatite, [ 10 ] zeolites, [ 11 ] Pd/DNA, [ 12,13 ] metal organic frameworks (MOFs), [ 14 ] organic polymers, [ 15 ] clays, [ 16 ] and bio‐supports [ 17,18 ] have been employed for as support for this purpose. In the recent years, palladium nanoparticles (PdNPs) have garnered tremendous attention in heterogeneous catalysis due to their excellent catalytic activity.…”
Section: Introductionmentioning
confidence: 99%